SYSTEMIC LESIONS OF LUNG TISSUE ELEMENTS IN PNEUMOCONIOSIS IN KUZBASS MINERS - Бондарев, Олег Иванович; Филимонов, Сергей Николаевич (Medicine in Kuzbass, 2023)
For many years, occupational disease in Russia remains very high, in Kuzbass it is almost 7-8 times higher than the overall level in the country. Up to 77.8 % of cases of occupational diseases (PB) in Kuzbass occur at coal mining enterprises, where up to 67.9 % of workers, mainly employed in underground work, work in the most unfavorable conditions (group III by sanitary condition). The problematic side of the issue of pneumoconiotic (PC) lesion is the lack of knowledge of the systemic mechanisms of the formation of pathological changes in the body, as well as methods for diagnosing pneumoconiosis [1]. The inconsistency of official ideas about the mechanisms of development and genetic aspects does not contribute to the further development of the PC problem and gives one-sidedness to its study. The indicated contradictions served as a motive for attempts to resolve them by pathomorphological examination of the lungs in dust pathology in miners. The purpose of the study – pathomorphological identification of the systemic pneumoconiotic process in the respiratory system. Material, methods and object of research. The research material was presented by lung tissue obtained during 50 forensic medical examinations of a group of miners (GS) who died simultaneously during work in a mine during a man-made disaster. The Control Group (GC) was formed from 30 cases of forensic medical examinations of Novokuznetsk men who died in a road accident, who were aged 25 to 55 years and had no visible organ pathology (ICD cipher – Z 03), including the results of autopsies. The object of the study was the histological and morphometric characteristics of the bronchi, respiratory tissue, pleura, arteries and veins of the small and large circulatory circles (MCC, BCC) available for light microscopy. Statistical processing was performed using the t-Student criterion for paired measurements, and the distribution of case frequencies in observation groups was compared by the value of χ2, and correlation analysis was also performed. Results. Pathomorphological changes in lung tissue under the influence of dust factor leads to systemic changes in all compartments of lung tissue, i.e. hemodynamic, air-conducting and respiratory components. Morphological evidence of consistency is characterized by the presence of atrophic bronchopathy, hypertrophy of smooth muscle cells in the pulmonary vessels and bronchi, changes in the interalveolar septa, macrophage reaction, diffuse fibroplastic changes in the pleura, bronchi and vessels. Conclusions. The simultaneous development of macrophage inflammation, granulomas, fibrosis in the respiratory structure of the lungs, as well as pleural lesions in combination with deposits of coal-rock dust are evidence of PC in miners who were considered practically healthy according to the results of PMT. Histological signs of patho-morphological changes in the vessels of the MCC in combination with atrophic bronchopathy can be considered diagnostic criteria of anthracosilicosis at its dorentgenological stage. Ethics. All studies of the deceased miners were based on the secondary examination of blocks and ready-made histological micro-preparations (glasses) of the material of the Bureau of Forensic Medical examination of Novokuznetsk, Osinniki, Prokopyevsk, Anjero-Sudzhensk. Studies of pathomorphological material were carried out strictly on the basis of Federal Law No. 323-FZ of 21.11.2011 «On the basics of protecting the health of citizens in the Russian Federation», in particular Article 67 «Conducting pathoanatomical autopsies».